Estrutura e composição da comunidade de abelhas Euglossini atraídas por iscas artificiais na Amazônia Meridional, Brasil - Souza, Marta Helena Schorn de (2014)
Euglossini, also known as orchid bees, are among the main pollinators in Neotropical forests, and their preservation is vital for survival and dynamics of natural areas. The finding community of that euglossines could be attracted with chemical substances similar to those produced by orchid flowers, enabled studies on the biology, diversity, genetics and distribution of these bees date in different locations. To determine the structure and species composition of the community of Euglossini bees attracted to different types of baits in the canopy and understory of the Amazon forest, we conducted two sampling during five consecutive days in October and December, 2012. Bees were collected in an area of native forest, where a study site is monitored in a long term (PPBio project www.ppbio.inpa.gov.br) in the municipality of Cotriguaçu, Mato Grosso state. Traps made of plastic bottles and containing pure chemical substances as baits (benzyl acetate, methyl cinnamate, cineole, eugenol, methyl salicylate and vanillin) were used. A total of 2.912 specimens, distributed in five genera and 41 species were registered. From the data two articles were generated. In the first article, entitled "Vertical distribution and attractiveness of odor baits in Euglossini bee communities (Hymenoptera: Apidae) in southern Amazonia", data species richness, species diversity, male abundance and species composition in two vertical forest strata using six different types of artificial baits are provided. The second article, entitled "Rediscovery of Eufriesea fragrocara (Hymenoptera: Apidae: Euglossini) in the Brazilian Amazon Forest", we expanded the geographic distribution of Ef. fragrocara about 500 Km to the east of the Amazon Basin.